PROSES FONOLOGIS DALAM PENGADOPSIAN KATA BAHASA INDONESIA KE DALAM BAHASA CIA CIA DI KABUPATEN BUTON, SULAWESI TENGGARA - Indrawati, Dianita (Universitas Negeri Surabaya, 2015)
This paper discusses the adoption of several phonological processes in Indonesian words into Ciacia in Buton, Southeast Sulawesi province. Ciacia language which is one of the languages with the most speakers in mainland Buton Kingdom in its development are adopting some Indonesian words. Adoption of words in Indonesian as compared to most other areas of the language word. This is due to ethnic mixing Ciacia just used both languages in daily life. In adopting Indonesian words into Ciacia many who have phonological processes. Phonological processes are most commonly found is the addition and removal of noise at the end of the word. The word has been adopted into the language Ciacia always be words with open syllables. This is caused by the language Ciacia unknown words with closed syllables.